IMPLEMENTASI ETIKA BISNIS ISLAM DALAM TRANSAKSI JUAL BELI DI MJ SWALAYAN KRAKSAAN PROBOLINGGO - Yeni Fatur Rohmah (IZZI: Jurnal Ekonomi Islam, 2022)
With the application of business ethics in running a business or economic activity, business executives or managers or general managers or directors of a business entity will be observant of the income or sales results. Along with the times, which are marked by very rapid economic developments, business competition is very high. With such high competition, business people use all means to gain profits, even business people often ignore ethics in running their business. so this study aims to find out how the concept and application of Islamic business ethics at mj supermarket kraksaan probolinggo by using data collection several techniques, namely: Observation (Observation), Interview (Interview),. And the method used to analyze the data in the research is to use the analytical method. In conclusion, the application of business ethics in general, as seen from the results of observations and interviews, has been applied at MJ supermarkets because MJ supermarkets already use soup, which means starting from how to dress, how to interact with consumers, etc., there are procedures that have been regulated by the management of the supermarket alone.